Malaysian youth well-being scale: development and initial validation - Zaremohzzabieh, Zeinab; D’Silva, Jeffrey Lawrence; Abu Samah, Asnarulkhadi; Dahalan, Dzuhailmi; Mohamed, Nor Aini; Mohamed Shaffril, Hayrol Azril (De la Salle University, 2019)
Youth well-being has become a phenomenon of interest to community youth workers. Despite the potential of youth well-being to promote positive youth outcome and strengthen community settings, the practice remains unfamiliar to many. Thus, this study used multidimensional constructs to measure youth well-being in Malaysia. The aims of this study were to (1) construct and validate a multidimensional measure of the Youth Well-Being Scale (YWS) and (2) scrutinize the psychometric and measurement properties of the YWS in Malaysian youths. A quantitative study was conducted to validate the 97-item YWS with a sample of 500 Malaysian youths. The YWS demonstrated adequate psychometric properties for 10 YWS dimensions in the exploratory factor analysis. Confirmatory factor analysis indicated that the multidimensional constructs fit the YWS data. Participants confirmed that the validity and reliability of youth well-being take place at the intersection of personal, relational, and collective strengths. Going forward, the analysis of results offers a big picture of community ideals, needs, strength, as well as potential actions that could enhance personal, relational, and collective wellbeing of youth in Malaysia.